Calf Blood Compound (CFC) and Homeopathic Drug Induce Differentiation of Primary Human Skeletal Muscle Cells - Langendorf, Eva K.; Klein, Anja; Rommens, Pol M.; Drees, Philipp; Ritz, Ulrike; Mattyasovszky, Stefan G. (International Journal of Sports Medicine, 2019)
The use of injections to treat structural muscle injuries is controversially discussed. In our controlled in vitro study, we investigated the biological impact of Actovegin and Traumeel alone and in combination on primary human skeletal muscle cells. Cells were characterized by immunofluorescence staining for myogenic factor 5 (Myf5) and MyoD, and cultured with or without Actovegin and / or Traumeel. The effects of these agents were assayed by cell viability and gene expression of the specific markers MyoD, Myf5, neural adhesion molecule (NCAM), and CD31. Myotube formation was determined by myosin staining. Neither Actovegin nor Traumeel showed toxic effects or influenced cell viability significantly. High volumes of Actovegin down-regulated gene expression of NCAM after 3 days but had no effect on MyoD, Myf5, and CD31 gene expression. High volumes of Traumeel inhibited MyoD gene expression after 3 days, whereas after 7 days MyoD expression was significantly up-regulated. The combination of both agents did not significantly influence cell viability or gene expression. This is the first study demonstrating that Actovegin and Traumeel potentially modulate human skeletal muscle cells. The relevance of these in vitro findings has to be highlighted in further in vivo studies.
Keywords: muscle injury; Calf Blood Copmpound®; Homeopathic Drug®